The effectiveness of forced-presentation method on students' learning experience / Ilyanie Hj Yaacob ... [et al.] - Hj Yaacob, Ilyanie; Jaafar, Zuraida; Wakid, Sarini Ahmad; Nawahwi, Mohd Zaini; Hasbullah, Nur Intan; Hasan, Nor'Aishah (UiTM Cawangan Johor, 2018)
The aim of this study is to attain more understanding about students' preference and perception on different methods of group presentation during lecture session. The study involved 97 students from Diploma in Microbiology in UiTM Cawangan Negeri Sembilan, Kampus Kuala Pilah. All students were exposed to two methods of group presentation, which are named as 'conventional- presentation method (CPM)' and 'forced-presentation method (FPM)'. Data were obtained from self-administered questionnaire which measured students' preparation, learning experience, assessment and overall satisfaction for both methods. The responses were measured using a 10-Point Interval Scale rating with 1 showed "strongly disagree" whilst 10 showed "strongly agree". Results showed that there are significant difference on perception between mean score of conventional-presentation method and the mean score of forced-presentation method for construct learning experiences, assessment, and overall satisfaction (p-values are less than 0.05). It can be concluded that students preferred forced-presentation method to enhance their learning experiences.